Ants as mealybug detectors: a novel tool for monitoring Planococcus ficus infestation based on ant behaviour. (15th December 2022) - Castracani, Cristina; Giannetti, Daniele; Spotti, Fiorenza A.; Schifani, Enrico; Ghizzoni, Martina; Delaiti, Marco; Penner, Francesco; Leonardi, Stefano; Mori, Alessandra; Ioriatti, Claudio; Grasso, Donato A.
Abstract: Vineyards are economically valuable agroecosystems that have spread to all continents. As such, sustainable management of their pests is an important goal. Mealybugs are serious pests of vines with Planococcus ficus (VMB) being the most problematic worldwide. Mealybugs are attended by different ant species, whose trophobiotic relationship is often considered damaging since some ant species may offer effective protection from natural enemies in exchange for honeydew. We tested whether this trophobiosis can be used as a VMB monitoring tool, developing a protocol to evaluate infestation on the plants based on ant behaviour (Ant method). We compared this new protocol with the conventional one, consisting in visual counting of VMBs on infested leaves (Leaf method). Our results demonstrated that the Ant method yielded significant advantages over the Leaf method by: (i) allowing to detect VMB infestation on individual plants much earlier; and (ii) allowing to keep track of VMB presence after pest treatments. The Ant method is proposed as a valid complementary tool for integrated pest management in vineyards and its successful achievement encourage searching for further agricultural contexts in which ants may be revaluated as a monitoring tool. Abstract : A new method based both on ant/mealybug trophobiosis and ant behaviour was developed for monitoring infestation of the vine mealybug (VMB) Planococcus ficus in Italian vineyards. In comparison with the conventional method based on direct count of P. ficus individuals on leaves, the new method is more sensitive in detecting infestation early in the season. In addition, the Ant method is more effective in detecting the residual presence of P. ficus after chemical treatments. Riassunto: I vigneti sono agroecosistemi rilevanti dal punto di vista economico e diffusi in tutti i continenti. Per questo motivo, la gestione sostenibile degli agenti infestanti di queste colture rappresenta un obiettivo di primaria importanza. Tra gli infestanti della vite, le cocciniglie rivestono un ruolo di primo piano e, in particolare, Planococcus ficus (VMB, la cocciniglia cotonosa della vite) è considerato il più problematico a livello globale. Le cocciniglie vivono a stretto contatto con diverse specie di formiche, con le quali instaurano una relazione di trofobiosi spesso considerata dannosa per le colture, in quanto le prime curano e proteggono le cocciniglie per ottenere in cambio la melata che esse producono. Questo lavoro ha testato la possibilità di utilizzare la trofobiosi come strumento per monitorare la presenza di cocciniglie sulle viti, sviluppando un protocollo che permette di rilevare l'infestazione attraverso l'osservazione del comportamento delle formiche (Metodo Formiche). Questo nuovo protocollo è stato, poi, confrontato con quello convenzionale, che consiste nell'ispezione di alcune foglie di piante infestate e nel conteggio degli individui di VMB presenti (Metodo Foglie). I risultati dimostrano che il Metodo Formiche presenta alcuni vantaggi significativi rispetto al Metodo Foglie, in quanto consente di rilevare l'infestazione sulle singole piante (i) molto più precocemente e (ii) anche in seguito al trattamento con pesticidi. Il Metodo Formiche rappresenta un valido strumento nell'ambito della gestione integrata degli agenti infestanti (Integrated Pest Management) dei vigneti. Questo risultato incoraggia quindi la ricerca di altri contesti agronomici in cui le formiche possano essere impiegate come strumenti di monitoraggio. Résumé: Les vignobles sont écosystèmes agricoles significatifs d'un point de vue économique et ils sont répandus dans tous les continents. Par conséquent, le management soutenable des agents envahissants de ces cultures représente un objectif de première importance. Les cochenilles figurent parmi les principaux agents envahissants des vignobles et, en particulier, Planococcus ficus (VMB, la cochenille cotonneuse de la vigne) est considéré le plus problématique au niveau global. Les cochenilles établissent une relation de trophobiose avec différentes espèces de fourmis et cette association est souvent considérée nuisible pour les cultures, parce que les fourmis protègent les cochenilles en échange du miellat qu'elles produisent. Dans cette étude, on a testé la possibilité d'employer la trophobiose comme un moyen pour monitorer la présence de cochenilles sur les vignes, en développant un protocole qui permit d'identifier l'infestation à travers l'observation du comportement des fourmis (Méthode Fourmis). Ce nouveau protocole a été comparé avec le conventionnel, qui prévoit l'observation de certaines feuilles des vignes infestées et le comptage des individus de VMB détectés (Méthode Feuilles). Les résultats montrent que la Méthode Fourmis présente certains avantages significatifs par rapport à la Méthode Feuilles, parce qu'elle permit de détecter l'infestation au niveau de chaque vigne (i) beaucoup plus précocement et (ii) même après le traitement avec des pesticides. La Méthode Fourmis est proposée comme un moyen efficace et complémentaire dans le cadre de la gestion intégrée des agents envahissants (Integrated Pest Management) des vignobles. Les encourageantes résultats obtenus avec sa mise en œuvre suggèrent l'importance de rechercher autres typologies d'écosystèmes agricoles où les fourmis peuvent être employées efficacement pour monitorer les infestations.